Respostas

2013-10-09T22:58:50-03:00
 \frac{17}{8} -  \frac{3}{1} = [( \frac{2}{3} + \frac{1}{2}) x^{2} - \frac{7}{4} ]
\frac{17}{8}- \frac{24}{8}=[( \frac{4}{6}  +  \frac{3}{6}) x^{2} - \frac{7}{4}
\frac{-7}{8}  = [ \frac{7 x^{2} }{6} -  \frac{7}{4} ]
\frac{-7}{8} +  \frac{7}{4} =  \frac{7 x^{2} }{6}
 \frac{-7}{8} + \frac{14}{8} =\frac{7 x^{2} }{6}
 \frac{7}{8} =\frac{7 x^{2} }{6}
7*6=8*7 x^{2}
42=56 x^{2}
x^{2} =42/56 (simplificando por 7)
x^{2} =6/8
 x^{2} =3/4
x= \sqrt{\frac{3}{4} }

PARCEIRO EU CHEGUEI NESSE RESULTADO AI RSRS, A PERGUNTA TBM TA MEIO CONFUSA